Malignant rhabdoid tumor in a solitary kidney arising in an adult patient with chronic obstructive renal calculi - Ayari, Y. (Int J Surg Case Rep, 2019)
INTRODUCTION: Malignant rhabdoid tumor (MRT) is one of the most aggressive and lethal malignancies in pediatric oncology, MRT of the kidney is an uncommon renal tumor in children and it’s extremely rare in adult patients. With only seven previously reported adult cases in the English-literature, to our knowledge this is the first case that is associated with renal calculi. PRESENTATION OF CASE: We present the case of a 65-year-old man with an MRT arising in a solitary kidney with multiple enlarged lymph nodes that compressing the inferior vena cava. DISCUSSION: Malignant rhabdoid tumor of the kidney was originally described as a “rhabdomyosarcomatoid” variant of Wilm’s tumor due to the resemblance of cells to rhabdomyoblasts, now this type of tumor is recognized as distant and unique malignant renal tumor. It affects usually children before the age of 2 years. Tumor tissue sampling is required to make the diagnosis of MRTK, based on either nephrectomy, core biopsy, or autopsy specimens. There is no established standard of care due to the paucity of cases. Surgery is considered to be the first choice of treatment if possible. CONCLUSION: This case report reinforces the importance of recognizing this entity in the adult population, and discuss the possible treatment options of this rare and highly aggressive tumor.